Suppressor of Cytokine Signaling-1/STAT1 Regulates Renal Inflammation in Mesangial Proliferative Glomerulonephritis Models - Bai, Jiuxu; Wu, Lingling; Chen, Xiaoniao; Wang, Liqiang; Li, Qinggang; Zhang, Yingjie; Wu, Jie; Cai, Guangyan; Chen, Xiangmei (Frontiers in Immunology, 2018)
Mesangial proliferative glomerulonephritis (MsGN) is a significant global threat to public health. Inflammation plays a crucial role in MsGN; however, the underlying mechanism remains unknown. Herein, we demonstrate that suppression of the cytokine signaling-1 (SOCS1)/signal transducer and activator of transcription 1 (STAT1) signaling pathway is associated with renal inflammation and renal injury in MsGN. Using MsGN rat (Thy1.1 GN) and mouse (Habu GN) models, renal SOCS1/STAT1 was determined to be associated with CD4+ T cell infiltration and related cytokines. In vitro, SOCS1 overexpression repressed IFN-γ-induced MHC class II and cytokine levels and STAT1 phosphorylation in mesangial cells. SOCS1 and STAT1 inhibitors significantly inhibited IFN-γ-induced CIITA promoter activity and MHC class II expression. In conclusion, our study emphasizes the pivotal role of the SOCS1/STAT1 axis in the regulation of inflammation in MsGN.